Wave‐Current Interactions During Hurricanes Earl and Igor in the Northwest Atlantic. Issue 12 (27th December 2021) - Lin, Shangfei; Sheng, Jinyu; Ohashi, Kyoko; Song, Qingtao
Abstract: Interactions between surface waves and ocean currents over the northwest Atlantic during Hurricanes Earl and Igor (2010) are investigated using a coupled wave‐circulation model and observational data. Our results show that the coupled model improves the model performance in simulating the surface waves, sea level, water temperature, and salinity. By including the wave‐current interactions (WCIs), the maximum significant wave heights (SWHs) are reduced by more than 10% along the storm tracks and more than 20% over eddies. In the Gulf of Maine (GoM), the simulated SWHs and peak wave periods are also modulated by strong tidal currents. Surface waves, in turn, reduce the semidiurnal tidal amplitudes (up to ∼9%) and currents (up to ∼40%) in the GoM due mainly to the wave‐enhanced bottom stress. Surface waves also increase the peak storm surge (up to ∼19%) during these hurricanes, which is mostly attributed to the wave‐induced forces through Stokes drift and wave dissipation but slightly compensated by the wave‐enhanced bottom stress. The hurricane‐driven surface currents are modulated by waves toward the clockwise direction with a decrease in current speeds of more than ∼60%. This is attributed to the reduced current shear and density gradient resulting from mixing enhanced by wave breaking, but compensated by wave‐induced forces. Salinity and temperature are also modulated by surface waves, mostly through the wave‐induced forces and enhanced mixing by wave breaking. Overall, the coupled model produces higher surface salinity and stronger surface cooling due to the inclusion of the WCIs. Plain Language Summary: Large surface waves generated by storms can have intense interactions with ocean currents. In this study, a coupled wave‐circulation model for the northwest Atlantic is used to investigate wave‐current interactions during Hurricanes Earl and Igor in September 2010. Our results demonstrate that the inclusion of wave‐current interactions in the numerical model improves the model performance over both deep waters and coastal regions. The maximum significant wave heights can be reduced by strong hurricane‐driven currents. Surface waves are also modulated by strong tidal currents in the Gulf of Maine (GoM) and by the Gulf Stream and Labrador Current. Surface waves, in turn, reduce the tidal amplitudes and tidal currents in the GoM and increase the peak storm surge during the two hurricanes. Surface waves also affect ocean currents and cause higher surface salinity and stronger surface cooling. Key Points: Modulations of waves by hurricane‐driven currents, near‐inertial currents, tides and large‐scale circulations Decrease of tidal amplitudes and currents due to wave‐enhanced bottom stress and increase of peak storm surges due to wave‐induced forces Hurricane‐driven currents are weakened by enhanced mixing due to wave breaking but strengthened by wave‐induced forces